Sustainable Transportation: The Constraints of An Italian Public University - D’Innocenzo, Massimiliano; Tozzi, Anna (Universitas Diponegoro, 2023)
In Italy most Universities are located in the City Centre, often in ancient buildings that are part of the architectural heritage. During the years they developed campuses in peripheral areas, or even in other cities of the region, thus the concept of “shuttle” takes on a special meaning. The sustainable transportation concerns two main issues: the commuting and the connection between the campuses. In both cases Universities in urban or city centre setting must rely on the services offered by the Municipality to all residents for mobility, and to their sustainable policies, that anyway are required by law. Even though the main problems and solutions do not depend directly on the Universities’ policies, the study highlighted some good practices have been produced.